2016
DOI: 10.1016/j.ijporl.2016.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial shape in children with and without a positive otitis media history

Abstract: Objectives Past studies using traditional morphometric approaches have reported a handful of differences in craniofacial dimensions between individuals with and without otitis media (OM). In this study, a geometric morphometry (GM) approach was used to determine if craniofacial shape is different among children with no history of OM and a history of recurrent acute OM (RAOM) at two different ages. Methods Nineteen standard landmarks were identified on lateral cephalometric radiographs from 79 children (41 Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Most recently, Gremba et al () performed a two‐dimensional geometric morphometric analysis of lateral X‐rays of children with and without otitis media at four (41 normal children and 38 with otitits media) and six years of age (27 normal and 25 with otitits media), comparing their bony airways via principal components analysis and discriminant function. It was found that individuals in the four year‐old group with otitis media differed significantly ( P < 0.035) in shape from nonsymptomatic children of the same age.…”
Section: Anatomical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Gremba et al () performed a two‐dimensional geometric morphometric analysis of lateral X‐rays of children with and without otitis media at four (41 normal children and 38 with otitits media) and six years of age (27 normal and 25 with otitits media), comparing their bony airways via principal components analysis and discriminant function. It was found that individuals in the four year‐old group with otitis media differed significantly ( P < 0.035) in shape from nonsymptomatic children of the same age.…”
Section: Anatomical Backgroundmentioning
confidence: 99%
“…None of these differences were found among the six year‐old sample of children with and without otitis media. Despite these interesting results, Gremba et al () collected data from lateral plain film radiographs, which does not account for the impact of mediolateral growth.…”
Section: Anatomical Backgroundmentioning
confidence: 99%
“…The collection was chosen as it is one of the largest available that spans in age from birth to the eruption of the first molar. Our growth series was designed to correspond to the time of peak OM incidence from birth until approximately 6 years of age (Gremba et al, 2016; Pagano et al, 2017; Takasaki et al, 2007), after which there is an associated clinical decline of OM occurrence (Casselbrant et al, 1986). The crania were divided into separate age groups using the dental eruption patterns from both the upper and lower jaw (see Table 2) applying the protocol of Moorrees, Fanning, and Hunt (1963) for eruption of the deciduous dentition.…”
Section: Methodsmentioning
confidence: 99%
“…The first of the cephalometric studies to utilize a geometric morphometric approach was Gremba and colleagues, (Gremba, Weinberg, Swarts, & Casselbrant, 2016) who analyzed shape differences among cohorts of 4‐year‐old children with and without recurrent OM and 6‐year‐old children with and without recurrent OM. Two‐dimensional bony landmarks distributed around the facial skeleton, cranial base, and mandible were collected from lateral radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…The ET, located deep within the head, is particularly challenging to assess and visualize, even with modern imaging technology, which perhaps explains the relatively few studies that directly compare its shape in groups with known diagnoses. Methodologies for evaluating the shape of this structure range from two-dimensional lateral radiographs [22] to three-dimensional quantification from dry skulls and CT imaging [23][24][25][26][27][28]. Past literature suggests that the angle of the ET changes dramatically from infancy to adulthood and that shape changes in the basicranium and nasopharynx coincide with the timing of peak OM incidence.…”
Section: Introductionmentioning
confidence: 99%